The effect of labor market regulations on training behaviour and quality : the German labor market reform as a natural experiment - Jansen, Anika [Verfasser]; Strupler Leiser, Mirjam [Verfasser]; Wenzelmann, Felix [Verfasser]; Wolter, Stefan C. [Verfasser] (My University, 2012)
"Labor market frictions are seen in many extensions of the classical human capital theory as a prerequisite for firms financing general training. The labor market reforms in Germany at the beginning of the millennium have therefore been seen by many as a danger to the firms' willingness to support the apprenticeship training system. This paper analyzes the training strategies German firms deployed to cope with the greater labor market flexibility as a result of the labor market reform. Switzerland where no reforms had taken place serves as the counterfactual. The results show that firms successfully reduced the net-costs of training by involving apprentices in more work and reducing non-productive tasks, like practicing. Contrary to the widespread fear, this adapted training strategy resulted also in a substantial increase in work-related competencies and productivity of apprentices." (Autorenreferat; BIBB-Doku)

Das Swiss Leading House "Economics of Education" hat untersucht, welche Auswirkungen Regulierungen des Arbeitsmarkts auf das Angebot und die Qualität beruflicher Ausbildung in Deutschland und der Schweiz haben. Die Studie kommt zum Schluss, dass die Lockerung von Regulierungen keinen negativen Einfluss hat. (BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 4 Kosten & Finanzierung; G 1.2 Arbeitsmarkt; I 2.2.1 Westeuropa; Arbeitsmarkt; Regulierung; Ausbildungsangebot; Berufsausbildung; Ausbildungsqualität; Ausbildungsverhalten; Betrieb; Finanzierung; Ausbildungsinvestition; Schweiz; Bundesrepublik Deutschland